Quick stops ebook - Smith, Kevin (Quick Stops (2022)., 2023)
Before there was a Marvel Cinematic Universe, DC Extended Universe, or Harry Potterverse; There was Kevin Smith's Askewniverse—a series of interconnected films featuring a cast of characters crossing over in multiple movies! And following on the heels of Clerks III, the Askewniverse is expanding with Quick Stops—a black and white anthology series full of all new tales of retail from the Jersey world of Kevin Smith's classic comedies! Featuring four never-before-told stores from the Quick Stop family of characters that populate Smith's films Mallrats, Chasing Amy, Dogma, Jay and Silent Bob Strike Back, Jay and Silent Bob Reboot, and of course, the Clerks trilogy! From the secret origin of where Holden McNeil got the idea for a Bluntman and Chronic comic from Jay & Silent Bob, to Elias and the parable of PillowPants, this collection of black and white comic shorts will be a must have book for any lifelong Clerks or Kevin Smith apologist! Collects Quick Stops issues #1–#4.